Investigating Misophonia: A Review of the Empirical Literature, Clinical Implications, and a Research Agenda - Brout, Jennifer J.; Edelstein, Miren; Erfanian, Mercede; Mannino, Michael; Miller, Lucy J.; Rouw, Romke; Kumar, Sukhbinder; Rosenthal, M. Zachary (Frontiers in Neuroscience, 2018)
Misophonia is a neurobehavioral syndrome phenotypically characterized by heightened autonomic nervous system arousal and negative emotional reactivity (e.g., irritation, anger, anxiety) in response to a decreased tolerance for specific sounds. The aims of this review are to (a) characterize the current state of the field of research on misophonia, (b) highlight what can be inferred from the small research literature to inform treatment of individuals with misophonia, and (c) outline an agenda for research on this topic. We extend previous reviews on this topic by critically reviewing the research investigating mechanisms of misophonia and differences between misophonia and other conditions. In addition, we integrate this small but growing literature with basic and applied research from other literatures in a cross-disciplinary manner.